Implementation of DKI Jakarta Provincial Regulation Number 4 of 2015 Concerning the Preservation of Betawi Culture (Case Study: Education Curriculum) - Ahmad Said Saputra; Iskandarsyah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
Based on DKI Jakarta Regional Regulation No. 4 of 2015 concerning Preservation of Betawi Culture in the education curriculum there is still no Betawi language education. As a result, not a few Betawi people don't care or even lack in preserving the Betawi language. Several solutions were generated to solve this problem, namely compiling a master plan for the preservation of Betawi language and literature. Purpose: to conduct a literature review that examines the implementation of DKI Jakarta Provincial Regulation No. 4 of 2015. Method: this literature study uses the narrative review method by analyzing various journals from the Garuda online database and Google Scholar relating to DKI Jakarta Provincial Regulation No. 4 of 2015. Conclusion: Lack of awareness of DKI Jakarta Culture Service officials and the Education and Community Service Office of the importance of researching and socializing the protection of the Betawi language